Alternative methods to measure the adhesive shear displacement in the thick adherend shear test. - Da Silvaa, L. F.; Da Silvaa, R. A. M.; Chousala, J. A. G.; Pintob, A. M. G.
There are standard tests to determine the adhesive properties, one of the most used being the Thick Adherend Shear Test (TAST). This test assumes that the adhesive deforms only in shear. The standard method recommends the use of a special extensometer attached to the specimen. The use of this extensometer needs a very experienced technician, in addition to requiring high costs of production. In this work, the adhesive shear deformation is measured with a conventional clip gauge used for tensile tests. The steel deformation correction is made using a non-contact method (optical)that gives only the adhesive deformation and a numerical analysis. The objective of this study was to evaluate the applicability of a simpler method of measuring the adhesive deformation and to evaluate methods without contact for the measurement of the deformation of thin adhesive layers. The results show that a simple clip gauge can be used to measure the adhesive deformation, provided a correction factor is applied.
Keywords: EPOXY; ACRYLIC; STEEL; LAP-SHEAR; MECHANICAL PROPERTIES; ADHESIVES; FINITE ELEMENT STRESS ANALYSIS; THICK ADHEREND SHEAR TEST